The Effect of home price on the geography of theft in Querétaro, Mexico: application of poisson point processes - San Román Tajonar, Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In this research, the theory of incivilities is tested to explain the formation of burglary hotspots in the Metropolitan Area of Querétaro. The data was obtained from an own survey and a web scraping application for the construction of spatial data. The relationship between the variables is investigated using a Poisson point process that attempts to explain the intensity of the phenomenon in a region. The results show that the price of housing maintains a negative relationship with the intensity of house robberies; Regarding incivilities, only graffiti and lawn maintenance matter.